Denosumab combined with precision radiotherapy for recurrent giant cell tumor of the thoracic spine: a case report and literature review - Miao, Zukang; Xu, Ming; Zheng, Kai; Gong, Hai; Yan, Ning; Chen, Qian; Yu, Xiuchun (Frontiers in Neurology, 2024)
Giant cell tumors of the spine have a high recurrence rate owing to their special anatomical site; hence, further treatment after recurrence is very challenging. Achieving effective tumor control and improving the long-term quality of life of the patients are the main treatment purposes to consider for recurrent giant cell tumors of the spine. A patient showing giant cell tumor recurrence of the thoracic spine after curettage received denosumab combined with precision radiotherapy, by which the tumor gained good control, and the patient could regain normal functioning. A review of the relevant literature suggested that denosumab combined with radiotherapy is an effective new approach for the treatment of recurrent giant cell tumors of the spine.